Pengaruh Penggunaan Media Edukasi Terhadap Tingkat Pengetahuan dan Sikap Siswa Mengenai Hipertensi - Dwi Helynarti Syurandhari; Asih Media Yuniarti; Widya Puspitasari; Shinta Nuraini (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Hypertension was a health problem that not only affected adults but was also increasingly found among adolescents. The low level of knowledge and preventive attitudes toward hypertension among students became an important issue that needed to be addressed through innovative educational methods. This study aimed to determine the effect of using an educational game-based medium, Uno Stacko, on students’ knowledge and attitudes regarding hypertension at MAN 2 Mojokerto Regency. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of students selected using total sampling technique. The instruments used were questionnaires measuring knowledge and attitudes. Data were analyzed using statistical tests to determine differences before and after the intervention. The results showed that students’ knowledge increased after the intervention, with the mean score rising from 63.1 to 82.5, and most respondents (66%) having good knowledge. Students’ attitudes also improved, with the mean score increasing from 26.98 to 47.01, and the majority of respondents (90%) demonstrating positive attitudes. The statistical test results showed a p-value of 0.000 (p<0.05), indicating a significant effect of the Uno Stacko educational media on students’ knowledge and attitudes. It was concluded that the Uno Stacko game-based educational media was effective in improving students’ knowledge and attitudes regarding hypertension. It was recommended that this interactive learning method be implemented continuously in school-based health education